Aprendizagem Musical Através de Composição Assistida por Computador - Isabela Corintha de Almeida (2018)
The formalization of musical structures has supported several computational strategies in the various levels of music teaching. This work intends to explore the potentialities of music technology in the apprehension of musical theory and practice in the context of tonal music for individuals without musical training, especially for children.Technically, an analysis-generation model will be explored, starting from examples of Western tonal system songs to capture stylistic rules that will serve to guide the user intuitively in the creation of new tonal musical structures.This dissertation deals with the integration of algorithms for algorithmic composition in an interactive musical system and proposes to offer a return to the user of the quality of musical creation in order to guide them in the cumulative acquisition of knowledge.